2009
DOI: 10.2478/s11686-009-0008-4
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Cryptosporidium hominis in pigeons (Columba livia)

Abstract: This study demonstrated the presence of Cryptosporidium hominis in pigeons for the first time. Previously, C. hominis had been cited only in another bird species, Branta canadiensis. The present findings suggest that pigeons may act as mechanical vectors for this protozoan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…C. parvum is known to have zoonotic potential and identification in birds is rare (Nakamura and Meireles, 2015). The literature on cryptosporidiosis in domestic birds is insufficient, but birds infected with C. meleagridis (Meng et al, 2011;Li et al, 2015), C. baileyi (Li et al, 2015) and Cryptosporidium hominis (Abreu-Acosta et al, 2009) have been reported from China and Spain, respectively. C. parvum has been occasionally reported from aquatic birds such as canada geese (Branta canadensis), mallard ducks (Anas platyrhynchos) (Graczyk et al, 1998), mandarin ducks (Aix galericulata), common mergansers (Mergus merganser) and mute swans (Cygnus olor) (Majewska et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. parvum is known to have zoonotic potential and identification in birds is rare (Nakamura and Meireles, 2015). The literature on cryptosporidiosis in domestic birds is insufficient, but birds infected with C. meleagridis (Meng et al, 2011;Li et al, 2015), C. baileyi (Li et al, 2015) and Cryptosporidium hominis (Abreu-Acosta et al, 2009) have been reported from China and Spain, respectively. C. parvum has been occasionally reported from aquatic birds such as canada geese (Branta canadensis), mallard ducks (Anas platyrhynchos) (Graczyk et al, 1998), mandarin ducks (Aix galericulata), common mergansers (Mergus merganser) and mute swans (Cygnus olor) (Majewska et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Birds belonging to the genus Columba may represent a public health concern, since they can potentially disseminate zoonotic pathogens and serve as reservoir of many parasitic diseases (Cooper, 1984;Kaminjolo et al, 1988;Piasecki, 2006;Lallo et al, 2012). Infections of domestic pigeons with helminths and coccidia have been reported in several regions of the world, such as in Turkey (Özkul and Aydin, 1994), Spain (Abreu-Acosta et al, 2009;Cano-Terriza et al, 2015), India (Gupta et al, 2011) and Iran (Radfar et al, 2012). In addition, infection with South and North America, Europe, Africa, Asia and Oceania (Nakamura and Meireles, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Due to perceived little importance of pigeons, little attention in terms of research has been directed towards the species. In many regions of the world, it has been reported that internal and external parasites and infections are common in pigeons (Senlik et al, 2005;Marques et al, 2007;Bunbury et al, 2008;Abreu-Acosta et al, 2009). Information on the parasitic infection of domesticated pigeons in different regions of Iran appears to be relatively little concerned with few published papers and presented mainly as conference proceedings or papers only about a single parasitic species (Youssefi et al, 2010;Pirali-Kheirabadi et al, 2008).…”
Section: Introductionmentioning
confidence: 94%
“…Within wild animals, much effort has been dedicated to investigating parasite burden in birds because of their potential for pathogen dispersal, with some avian parasites being highly pathogenic to humans, for example avian influenza, West Nile virus, chlamydiosis and cryptosporidiosis (Kurt et al, 2003;Dhama et al, 2008;Abreu-Acosta et al, 2009). Emerging diseases can have a severe impact on bird species and populations (Robinson et al, 2010), a problem that is particularly pronounced for taxa with restricted distributions, such as endemic land bird species inhabiting oceanic islands (van Riper et al, 1986;Carrete et al, 2009).…”
Section: Introductionmentioning
confidence: 99%